COL2-dependent photoperiodic floral induction in Nicotiana sylvestris seems to be lost in the N. sylvestris × N. tomentosiformis hybrid N. tabacum - Schmidt, Florentin J.; Grundmann, Lena; Lahme, Michael; Seidemann, Marvin; Schwarze, Axel; Lichtenauer, Sophie; Twyman, Richard M.; Prüfer, Dirk; Noll, Gundula A. (Frontiers in Plant Science, 2024)
Plants are sessile organisms that maximize reproductive success by adapting to their environment. One of the key steps in the reproductive phase of angiosperms is flower development, which requires the perception of multiple endogenous and exogenous signals and their integration via a complex regulatory network. The key floral regulators are known in many species, including the main transcription factor of the photoperiodic pathway (CONSTANS, CO) and the central floral pathway integrator (FLOWERING LOCUS T, FT). We identified several CO-like (COL) proteins in tobacco (Nicotiana tabacum). In the day-neutral plant N. tabacum, the NtCOL2a/b proteins were the most closely related to Arabidopsis CO. We characterized the diurnal expression profiles of the corresponding genes in leaves under both short-day (SD) and long-day (LD) conditions and confirmed their expression in phloem companion cells. Furthermore, the orthologs of NtCOL2a/b in the maternal LD ancestor (N. sylvestris) and paternal, facultative SD ancestor (N. tomentosiformis) of N. tabacum were expressed in the same diurnal manner. NtCOL2a/b-overexpression or knock-out using the CRISPR/Cas9 system did not support a substantial role for the CO homologs in the control of floral transition in N. tabacum. However, NsCOL2 overexpression induced flowering in N. sylvestris under typically non-inductive SD conditions, correlating with the upregulation of the endogenous NsFTd gene. Our results suggest that NsFTd is transcriptionally regulated by NsCOL2, providing insight into the diverse genetics of photoperiod-dependent flowering in different Nicotiana species.